2017
DOI: 10.26418/jebik.v6i3.23256
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Belanja Daerah Berdasarkan Klasifikasi Ekonomi terhadap Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat di Kabupaten/Kota Provinsi Kalimantan Barat Tahun 2010 - 2015

Abstract: This study aims to examine and analyze the influence of local goverment expenditure based on economic classification consisting of personnel expenditure, capital expenditure, goods and services expenditure, grant expenditure and social assistance expenditure on economic growth and social welfare in the regency/city of West Borneo Province. The data in the study used panel data consisting of time series data (2010 -2015) and cross-section data (14 regency/city in West Borneo Province). Hypothesis testing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 0 publications
2
16
1
17
Order By: Relevance
“…The results of this study support the research (Herlina, 2013) Regional Expenditure have not significant influence on Gross Regional Domestic Products, but not support the research (Deviani, 2016); (Deswantoro, 2017) found Regional Expenditure have significant influence on Gross Regional Domestic Products.…”
Section: Test the Influence Of The Dominant Factors That Influence Recontrasting
confidence: 86%
See 2 more Smart Citations
“…The results of this study support the research (Herlina, 2013) Regional Expenditure have not significant influence on Gross Regional Domestic Products, but not support the research (Deviani, 2016); (Deswantoro, 2017) found Regional Expenditure have significant influence on Gross Regional Domestic Products.…”
Section: Test the Influence Of The Dominant Factors That Influence Recontrasting
confidence: 86%
“…The contradiction is research (Herlina, 2013); (Tahar & Zakhiya, 2011) found Regional Own Revenue, General Allocation Fund and Revenue Sharing Fund have not significant influence on Gross Regional Domestic Products. The relationship between variable Regional Expenditures and Gross Regional Domestic Product is formulated based on the results of the study (Deviani, 2016); (Deswantoro, 2017) found Regional Expenditure have significant influence on Gross Regional Domestic Products. The contradiction is research (Herlina, 2013) Regional Expenditure have not significant influence on Gross Regional Domestic Products.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Keynesian theory, government spending affects economic development, which is supported by the results of studies of previous researchers. Government expenditure in the form of salaries will affect employee consumption of a product so that it affects economic activity to produce these products (Deswantoro, Ismail, & Hendarmin, 2017). The results of other studies show that indirect spending, one of which is personnel expenditure, has not been able to spur economic growth (Lantu et al, 2019).…”
Section: Hypothesis Personnel Expenditurementioning
confidence: 99%
“…ISSN : 2337-3067 E-Jurnal Ekonomi dan Bisnis Universitas Udayana 9.6 (2020):485-508 (Deviani, 2016) yang menyebutkan bahwa belanja rutin dan belanja investasi tidak berpengaruh sedangkan belanja pembangunan berpengaruh terhadap pertumbuhan ekonomi, sedangkan penelitian yang dilakukan (Jiranyakul, Komain and Brahmasrene, 2007) mengambil kesimpulan bahwa belanja pemerintah mempunyai pengaruh terhadap pertumbuhan ekonomi namun tidak sebaliknya. Berdasarkan penelitian (Deswantoro, 2017)…”
Section: Pendahuluanunclassified